Cultural resource stewardship at Fishers Peak State Park - Rose, Shaun, author (Colorado State University. Libraries, 2021)
The following thesis comes from research undertaken on a contract with Colorado Parks and Wildlife to deliver a cultural resource stewardship chapter for park managers. Additionally, the scope of work called for three oral histories, two field surveys and four historic preservation inventory forms, GIS shapefiles, and interpretive recommendations. The project began as the major writing assignment for my graduate U.S. history Research Seminar and continued as a summer internship with CSU's Public Lands History Center (PLHC). I conducted initial research between February and April 2021 and drafted an article-length narrative by May. I continued research between May and August. We conducted fieldwork at Fishers Peak State Park, and I also spent a day at the Steelworks Center of the West archive in Pueblo. Despite the conflict and violence prevalent over the past 12,000 years in Southeastern Colorado, all peoples nevertheless shared an underlying trust that the land in this region was good for something, and that human ingenuity could unlock that value. Consequently, Fishers Peak's history is scarred from violence yet also decorated with examples of brief but meaningful collaboration. Because 19,200 acres surrounding Fishers Peak comprises Colorado's newest State Park with many recreational uses and subsequent potential for damage, it is more important now, than ever, to research, interpret, and delineate the space's cultural significance for its various inhabitants. The narrative history, interpretive recommendations, and maps we delivered through this project will help park staff effectively manage Fishers Peak's cultural resources into the indefinite future.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: cultural resource management; public lands; Fishers Peak State Park